Analysis of technological developments and potential of biomass gasification as a viable industrial process : A review - Erdiwansyah, E.; Gani, Asri; Zaki, Muhammad; Rizalman, Mamat; Nizar, Muhammad; Mohd Rosdi, Salleh; Yana, Syaifuddin; Sardjono, Ratnaningsih Eko (Elsevier Ltd, 2023)
They use technologies for the thermochemical conversion of substances for biomass, like pyrolysis, torrefaction, gasification, and hydrothermal process. In recent years, the generation of synthetic gas has significantly developed. This is especially true when associated with the biomass gasification processes, primarily related to syngas production. The review focuses on technologies for cleaning syngas, gasification processes, and simulation methods on procedure parameters. In conclusion, prospect growths and opportunities are investigated, and discussions culminate with the presentation of a novel hydrogen fabrication strategy predicated on utilizing a modified combustion process that operates with such an air deficit.